Kajian Kemampuan Berpikir Kritis (Critical Thinking Skill) Dari Sudut Pandang Filsafat - Adhitya Rahardhian (Undiksha, 2022)
Critical thinking is one of the higher-order thinking skills needed in developing 21st CenturySkills. Education as an effort to educate the nation's life places the ability to think as a necessarycompetency. The purpose of the education system is to form educated people who are independent and can think effectively and critically. Every individual need critical thinking skill tosolve problems in difficult situations. The roots of critical thinking are as ancient as the beginningof philosophical thought. About 2500 years ago, Socrates discovered the method of inquiry(probing questioning). The concept of critical thinking then developed to the current era. Thedevelopment concept of critical thinking from the point of view of philosophy is important to study to gain a holistic understanding of the critical thinking framework. The method used to compile this article is library research. Several definitions of critical thinking of mutually supportive or complementary. The concept of thinking in a critical review on the nature, attitude, and quality of thinking. The concept of critical thinking is eight things, namely: analysis, reasoning, inference, comparison, hypothesis, synthesis (new ideas), testing, and comprehensive conclusions.